2018
DOI: 10.3389/fpsyt.2018.00645
|View full text |Cite
|
Sign up to set email alerts
|

Early Linguistic Markers of Trauma-Specific Processing Predict Post-trauma Adjustment

Abstract: Identifying early predictors for psychiatric disorders, such as post-traumatic stress disorder (PTSD), is crucial for effective treatment and prevention efforts. Obtaining such predictors is challenging and methodologically limited, for example by individuals' distress, arousal, and reduced introspective ability. We investigated the predictive power of language-based, implicit markers of psychological processes (N = 163) derived from computerized text-analysis of trauma and control narratives provided within 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 42 publications
5
56
0
Order By: Relevance
“…Markers of working through can be measured by a group of words, which include insight words (e.g., understand, meaning), causal words (e.g., because, result), and selfdiscrepancy or modal words (e.g., would, should). Multiple studies have found that cognitive processing words are connected to the ways people process traumatic events (24)(25)(26). Researchers hypothesize that cognitive words are used at greater rates to describe negative events because people are in the middle of figuring out why the event occurred and to ultimately produce a coherent narrative (27).…”
Section: Significancementioning
confidence: 99%
“…Markers of working through can be measured by a group of words, which include insight words (e.g., understand, meaning), causal words (e.g., because, result), and selfdiscrepancy or modal words (e.g., would, should). Multiple studies have found that cognitive processing words are connected to the ways people process traumatic events (24)(25)(26). Researchers hypothesize that cognitive words are used at greater rates to describe negative events because people are in the middle of figuring out why the event occurred and to ultimately produce a coherent narrative (27).…”
Section: Significancementioning
confidence: 99%
“…The LIWC cognitive process index, which captures the frequency of words such as think, question, and because. This index is believed to indicate individuals' efforts to analyze or mentally organize experience 64 .…”
Section: Studymentioning
confidence: 99%
“…More frequent use of first-person singular (eg, I ) and negative emotion words and marginally fewer positive emotion words have been identified in those experiencing depression [ 19 , 20 ]. Greater use of cognitive processing words (eg, because and realization ) predicts fewer posttraumatic stress disorder symptoms among trauma survivors [ 21 ], and in our own research, third-person plural use (eg, we ) is higher in groups with lower EE [ 22 ]. Taking this research together, we expected participants with concerning levels of EE at baseline to use more first-person singular and negative emotion words and fewer third-person plural, positive emotion, and cognitive processing words in their letters.…”
Section: Introductionmentioning
confidence: 97%